Proceedings of the International Summer School on Experimental Physics of Gravitational Waves, Urbino, Italy, September 6-18, 1999 - Barone, M. (Maura) (World Scientific, 2000)
This book introduces needed theoretical instruments and offers an up-to-date discussion on fundamental physics as well as the experimental tools used and developed for the construction and exploitation of gravitational wave antennae (resonant bars, ground-based and space interferometric detectors). In addition, problems in the fields of optics, signal processing, control and feedback in active mechanical filtering are deeply analyzed, with reference to recent solutions adopted in the main detectors.